A Creative Pedagogue's Inquiry through Images: Does it Have Wings? - Rajabali, Anar (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2021)
In this photo essay, I enact how a creative pedagogue engages with artistic practice and contemplative inquiry. As a poet, at home in words, photography represents a creative risk. This vulnerability is felt in the sharing of the work through the lens of (re)search. Hence, I ask: Does it have wings? By delving in expressive forms toward the service of understanding my personal and pedagogical self, creative risk is rewarded in profound ways. I have discovered that my art practice is driven by intention, intuition and imagination. Thus, here is my creative pedagogy in action illuminating how an inquiry through images provokes learning and teaching. Both poetry and photography provide keen vision—a way of sensing and seeing Light.